Fertility Histories and Heart Disease in Later Life in China - Wu, Yuanyang; Pang, Jiahui; Wang, Jiahao; Wu, Jing; Zhang, Shuo; Zhang, Siqing; Yao, Yidan; Cheng, Simeng; Tao, Yiwen; Shen, Zheng; Li, Zhi-yun; Xie, Lin; et al. (Frontiers in Public Health, 2022)
Purpose Based on life course theories, health among older people is driven by a continuous and cumulative process that develops over the life course. To better understand the aging process, it is important to assess associations between parity and heart disease in older people of China. Method The associations between heart disease prevalence and number of births, number of boys or girls ever born were evaluated among 5,990 samples (mean age 64.1 years) using the Probit regression model based on the data from China Health and Retirement Longitudinal Study (CHARLS) conducted in 2013 and 2018. The model was adjusted only for rural or urban residents, and multivariate regression models were run separately by gender. Results Our results showed that more than three children or more than two boys ever born were associated with a higher risk of heart disease. However, the number of girls ever born had no significant effect on heart disease in the elderly. We further analyzed the group difference between urban and rural residents using the regression model. More than three children or more than two boys ever born were associated with a high risk of heart disease in rural areas. Compared to urban residents, rural residents were more likely to be suffering from heart disease due to high parity. When considering the digender difference the paper found that more than three children ever born were associated with a high risk of heart disease in the female group. Late age at the time of giving birth for the first time was associated with a poorer risk level of heart disease in the rural residents, because the phenomenon of early childbearing was serious in the rural residents. But after considering the impact on the physical health of using chronic diseases, the first birth and the last birth both increased the risk of heart disease. Conclusions Some policy implications were being put forward. Firstly, parents who were ready to give birth should be aware of the possible health loss of high parity. Postpartum nutrition supplements and chronic disease prevention were suggested to prevent heart disease in later life. Secondly, the elderly in rural areas should pay more attention to heart diseases. Participating in more daily exercise and physical examinations was a good choice to reduce the risk of heart disease. Thirdly, women who give birth prematurely have a higher risk of CVD. Based on our results, age at entry to parenthood was closely related to the risk of heart disease in later life.